CULTURE-BASED UMKM EMPOWERMENT THROUGH COLLABORATIVE GOVERNANCE: A CASE STUDY OF WIT-WITAN MARKET, ALASMALANG VILLAGE, BANYUWANGI - Zahra Nurkhawarin; Ika Devy Pramudiana; Sapto Pramono; Sri Kamariyah (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the empowerment of culture-based MSMEs in Wit-Witan Market, Alasmalang Village, Banyuwangi Regency, from a state administration perspective. Wit-Witan Market is a local economic development model that integrates the preservation of the Osing Tribe's cultural identity with productive economic activities. Using a descriptive qualitative approach, this study examines how cultural capital in the form of traditional culinary, traditional clothing, and the concept of an environmentally friendly market is converted into economic capital with high bargaining power. The results show that empowerment in Wit-Witan Market applies a bottom-up scheme that places the community as the main actor, while the village government acts as a facilitator through collaborative governance involving Pokdarwis, BUMDes, and local residents. This integration has succeeded in creating a new economic space that improves community welfare without eliminating the authenticity of local traditions. However, this study also identified several crucial challenges, namely fluctuations in traders' income influenced by weather factors and seasonal visits, as well as the inconsistency of managerial capacity building and digital financial literacy programs from related agencies. Theoretically, the success of the Wit-Witan Market reflects the effectiveness of the implementation of Community-Based Tourism (CBT) and collaborative governance in creating sustainable economic independence. Although it has become a good practice in local wisdom-based economic development, it is necessary to strengthen the commitment to collaboration, continuously scheduled mentoring, and periodic evaluation to ensure the sustainability of the economic and social impacts for the local community in the future.